The relationship between operation duration and shivering in post-spinal anaesthesia patients - Renaningtyastutik, Yuli; Lumadi, Sih Ageng; Handian, Feriana Ira (Palembang MediRose Publisher, 2022)
Background: Giving spinal anaesthesia is an effort to relieve pain to create optimal conditions for surgery operation consciously. A shivering event frequently follows the phenomenon of the long duration of the operation. Purpose: The study aimed to determine the relationship between operation duration and shivering in post spinal anaesthesia patients. Methods: The study design is a quantitative study and uses a cross-sectional approach. Sampling used a systematic sampling technique on the population of patients undergoing surgery under spinal anaesthesia. The instrument used Croessley and Mahajan’s observation sheet. This study uses Spearman rank rho as the statistical test with a significant value of p=0.05. Results: The study showed almost respondents, as many as 86.15 respondents (56 patients) experienced shivering. Based on the Spearman statistical test, the p-value is 0.046. Conclusions: It can be concluded that there was a relationship between operation duration and incidence of shivering. Therefore, to reduce the occurrence of shivering, it is necessary to take measures such as giving warm blankets, warm fluids, and tools to maintain body temperature (force air warming).